2019
DOI: 10.1002/ajh.25459
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban for the prevention of thromboembolism in immunomodulatory‐treated myeloma patients: Myelaxat, a phase 2 pilot study

Abstract: The risk of venous thromboembolism (VTE) is higher in myeloma patients receiving immunomodulatory compounds. A VTE prophylaxis using low‐molecular‐weight heparin or aspirin is therefore proposed. Apixaban is an oral direct anti‐Xa. Several studies have shown the efficacy and safety of apixaban in VTE prophylaxis compared to enoxaparin. The objective of this prospective phase 2 pilot study was to assess the risk of VTE and bleeding in patients with myeloma treated with immunomodulatory compounds lenalidomide (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 24 publications
1
30
0
2
Order By: Relevance
“…Pergourie et al also recently presented data from the use of apixaban as prophylaxis in MM patients on IMiDs. Two events were reported among 140 patients receiving apixaban 2.5 mg twice daily over six months [97]. DOACs are substrates of P-glycoprotein and P450; therefore an important issue to note with their use compared to the other classes of drugs is the potential drug-drug interactions.…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
“…Pergourie et al also recently presented data from the use of apixaban as prophylaxis in MM patients on IMiDs. Two events were reported among 140 patients receiving apixaban 2.5 mg twice daily over six months [97]. DOACs are substrates of P-glycoprotein and P450; therefore an important issue to note with their use compared to the other classes of drugs is the potential drug-drug interactions.…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
“…Several studies have in fact shown a promising efficacy of the new oral anticoagulants (DOACs) in preventing thrombosis in cancer patients, including MM [40,49,51,55]. Recent studies also showed that apixaban, especially at low dose, was safe and effective for thromboprophylaxis in relatively small series of MM patients receiving an IMiD-containing regimen as first line treatment or for relapsed disease [53]. Therefore, although further studies are needed for evaluating the role of DOACs in VTE prophylaxis in MM patients and possible drug interactions between DOACs and specific myeloma treatment, including supportive medications, these drugs seem to be at least as effective as LMWH and are an attractive alternative for thromboprophylaxis in MM since they do not require monitoring and spare patents from daily injection [48].…”
Section: Discussionmentioning
confidence: 99%
“…According to the consensus statement from the International Myeloma Working Group, patients receiving immunomodulatory drugs should be administered appropriate thromboprophylaxis (either antiplatelet or anticoagulation pharmacotherapy) based on their individual risk factors for the first 4 to 6 months of treatment [74]. In a recent phase 2 pilot study the non-vitamin K oral anticoagulant apixaban was used for thromboprophylaxis in multiple myeloma patients who were receiving immunomodulatory drugs with promising results [75]. Practically, thromboprophylaxis in often maintained while the risk for thromboembolism remains high, and as long as it is tolerated by the patient, avoiding bleeding complications.…”
Section: Cardiac Side Effects Of Amyloid-targeted Therapiesmentioning
confidence: 99%